Relaxation Time in CDP Model Used for Analyses of RC Structures. (2017) - Szczecina, Michał; Winnicki, Andrzej
Abstract: Concrete damaged plasticity (CDP) model is one of the most popular material models for plain and reinforced concrete implemented in Abaqus software. It is theoretically described by Lubliner et al. and Lee and Fenves. Use of this model requires values of some material constants. The choice of proper values of these constants is still an opened scientific issue and should be discussed. The article discusses a very important CDP parameter, namely relaxation time (for viscoplastic regularization) with respect to loading time. It is proven that too high value of relaxation time or too small loading time can lead to an overestimation of tensile strength of concrete. The analysis of this problem is performed in Abaqus in a tension test similar to laboratory tests by Woliński. The correctness of the calibrated CDP parameters is then checked in Abaqus for an element in complex stress state, namely for reinforced concrete frame corner under opening bending moment. The analyzed corner has different reinforcement details and different section heights of elements joining in it. Both SLS and ULS are checked and the propagation and width of cracks is recreated. Moreover, authors of this paper checked a relationship between reinforcement ratio and corner efficiency factor and then compared it with results presented by McGregor and Campana et al.